2005
DOI: 10.1002/adem.200400183
|View full text |Cite
|
Sign up to set email alerts
|

FePt Hard Magnets

Abstract: The FePt alloys have recently attracted considerable attention due to their excellent intrinsic magnetic, chemical and mechanical properties. Their possible usage ranges from permanent magnets for special applications (e.g. in micro‐electro‐mechanical systems, magnetic MEMS, and in aggressive environments) to ultra‐high density magnetic storage media. The article describes general aspects concerning the phase formation and magnetic properties of materials based on the L10 FePt phase. Both thin film and bulk ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
109
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(112 citation statements)
references
References 20 publications
(25 reference statements)
1
109
0
2
Order By: Relevance
“…In the Ref. [16], it has been reported that the tetragonal phase is usually identified by an occurrence of the superlattice reflections (001) and (110) of the fct-lattice representing unambiguously the L10 phase. These two superlattice peaks occur in Figure 2 at 2θ about 24° and 33°, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the Ref. [16], it has been reported that the tetragonal phase is usually identified by an occurrence of the superlattice reflections (001) and (110) of the fct-lattice representing unambiguously the L10 phase. These two superlattice peaks occur in Figure 2 at 2θ about 24° and 33°, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We confirmed that remanence enhancement occurred in the sample because of the saturation magnetization of 1.43 T for Fe 50 Pt 50 ordered phase. 8 As shown in Fig. 6, the recoil rate of the Fe-Pt thick film shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We considered that the increase in the substrate temperature enabled us to achieve the rapid rise in coercivity by taking advantage of the order-disorder transformation and that the gradual reduction was attributed to the formation of Fe 3 Pt as a soft magnetic phase. 8 We succeeded in obtaining L1 0 ordered phase and relatively high coercivity by using a suitable laser power without using a substrate heating system and a post-annealing process. , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] High uniaxial magnetocrystalline anisotropy of the L1 0 FePt phase is one of the key properties for those applications. 8 Unfortunately, as-synthesized FePt particles take a disordered A1 structure which has vanishingly small magnetocrystalline anisotropy. Therefore postsynthesis annealing is necessary to transform the disordered A1 phase to the ordered L1 0 phase.…”
Section: Introductionmentioning
confidence: 99%